Study The Effect of Increase Exposure Distance to Power and Beam Diameter in CO2Laser - Khalil Ibrahim Mohammed (Tikrit Journal of Pure Science)
In this research, a practical determination of the power in CO2 laser at every value from the operating current had been studied. The measurement had been carried out through the calculations of the temperature produced by the laser beam, in addition, the effect of the distance between the leaser generator and the target had been measured, furthermore, increase of the spot diameter was studied at the increase of the distance between the laser device and the target  surface.